1998
DOI: 10.1093/oxfordjournals.jbchem.a021939
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Both Oleosin Isoforms on the Surface of Seed Oil Bodies and Their Individual Stabilization to the Organelles

Abstract: The oil bodies of plant seeds contain a triacylglycerol matrix surrounded by a monolayer of phospholipids embedded with alkaline proteins termed oleosins. Two distinct oleosin isoforms with molecular masses of 18 and 16 kDa are present in rice oil bodies. Chicken antibodies raised against oleosin 18 kDa and rabbit antibodies raised against oleosin 16 kDa did not cross-recognize these two homologous isoforms. This peculiar non-cross recognition was used to locate the two oleosin isoforms on the surface of oil b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 0 publications
1
34
1
2
Order By: Relevance
“…The result is in accord with that obtained with reconstituted oil bodies and rice oleosin isoforms. 10) Nevertheless, none of the oil bodies reconstituted under our experimental conditions maintained their integrity as natural seed oil bodies puriˆed from mature sesame seeds did, presumably because of imperfect reconstitution.…”
Section: Stability Of Reconstituted Oil Bodies As Ašected By Sesame Omentioning
confidence: 73%
“…The result is in accord with that obtained with reconstituted oil bodies and rice oleosin isoforms. 10) Nevertheless, none of the oil bodies reconstituted under our experimental conditions maintained their integrity as natural seed oil bodies puriˆed from mature sesame seeds did, presumably because of imperfect reconstitution.…”
Section: Stability Of Reconstituted Oil Bodies As Ašected By Sesame Omentioning
confidence: 73%
“…Two distinct classes, H-and L-(high and low molecular weight) oleosins, are present in seed oil bodies of diverse angiosperms, and one or more isoforms may occur in each oleosin class of the same species [123]. It has been shown that H-and L-oleosins coexist on the surface of each oil body in seed cells of sesame [124]. The main difference between these two oleosin isoforms is an insertion of 18 residues in the C-terminal domain of H-oleosin, accounting for a 2 kDa difference in mass between the two classes found in many species [125][126][127].…”
Section: Oleosin Isoformsmentioning
confidence: 99%
“…The non-fusion recombinant cystatin over-expressed in E. coli was resolved by glycine-SDS-PAGE 19) and eluted according to the gel extraction method. 20) Antibodies against the recombinant nonfusion cystatin were raised in chickens, and immunoglobulins were purified from egg yolk for immunoassays. 21) In these immunoassays, the proteins resolved by SDS-PAGE were transferred on to a nitrocellulose membrane (Pall, Ann Arbor, MI, USA) in a Trans-Blot system (Bio-Rad, Hercules, CA, USA) according to the manufacturer's instructions.…”
mentioning
confidence: 99%